Systemic Management Practices—Enabling Local Governments to Adapt in Response to Complexity - Manuel Riemer; Randy Sa’d; Tim Posselt; Pourya Salehi; David Corbett; Peter Jones; Antony Upward; Exmond DeCruz; Bill Baue; Asad Asadzadeh; Simone Sandholz; Theo Kötter (World, 2025)
Local governments are increasingly navigating accelerating change and escalating complexity caused by interconnected crises, commonly referred to as a global polycrisis. These crises, including climate change, lack of affordable housing, declining mental health, and geopolitical instability, both shape and are shaped by local conditions. Cities face growing pressure to equitably provide services that are responsive to evolving community needs while contending with the systemic nature of contemporary challenges. However, local governments are often constrained by conventional management frameworks and practices that do not match the complexity of today’s challenges. The purpose of this conceptual paper is to explore how systems science can be leveraged to define and characterize a transformative new type of management designed to enable local governments to more adequately address emerging complexity. To this end, the authors review the literature on contemporary management practice and explore how management for local government can be reframed in alignment with the insights from systems science, using a service ecosystem lens. The findings point to a needed shift toward systemic management practices that are integrative, collective, and adaptive. The authors illustrate the practical relevance of these three characteristics and conclude with recommendations for research, policy, and practice aimed at building the institutional capabilities required to transition toward systemic management frameworks and practices that match the complexity of the polycrisis.